Complete mitochondrial genome organization of Schizothorax plagiostomus (Heckel, 1838). (2nd January 2016) - Goel, Chirag; Sahoo, Prabhati Kumari; Barat, Ashoktaru
Abstract: The complete mitochondrial genome of Schizothorax plagiostomus, an endemic coldwater fish of Himalayas, was determined for the first time. The genome is 16, 576 bp in length and consists of 13 protein coding genes, 22 tRNAs, 2rRNA genes and 1 putative control region. The gene organization and its order were similar to other vertebrates. The overall base composition was A 30%, G 17.4%, C 26.8%, T 25.8%, A + T content 55.8% and the G + C content 44.2%. The control region consists of a microsatellite locus (TA)12 between 16, 460 and 16, 483 bp. The present study will provide the rationale for the management and conservation of S. plagiostomus .